Changes in Frequency and Activation Status of Major CD4+ T-Cell Subsets after Initiation of Immunosuppressive Therapy in a Patient with New Diagnosis Childhood-Onset Systemic Lupus Erythematosus - Singla, Saimun; Wenderfer, Scott E.; Muscal, Eyal; Sagcal-Gironella, Anna Carmela P.; Orange, Jordan S.; Makedonas, George (Frontiers in Pediatrics, 2017)
Background: Several studies suggest that defects of regulatory T-cells (Tregs) and impaired cellular immunity are secondary to an imbalance between auto-aggressive T-cells and Tregs in lupus patients. These discrepancies in Tregs and effector T-cells (Teff) in active lupus patients are shown to be restored in patients upon receiving immunosuppressive therapy. Therefore, our main aim was to observe frequencies of these CD4+ T-cell subsets and Tregs/Teff ratio in a new diagnosis of childhood-onset systemic lupus erythematous (cSLE) before and after initiation of therapy. We also monitored T-cell exhaustion status by examining responses to super-antigen Staphylococcal Enterotoxin B (SEB) and PD-1 expression in this patient. Methods: Phenotyping of CD4+ T-cell subsets was carried out under basal conditions and after SEB stimulation using flow cytometry in one inactive (I-cSLE) and one active cSLE (A-cSLE) patient, and a healthy control (HC). The A-cSLE patient was a new diagnosis. Variables were measured at three consecutive time points in the active patient, reflecting various stages of disease activity. Activation status of CD4+ T-cells in the A-cSLE patient was compared to that of the I-cSLE patient and HC. Disease activity was measured by calculating the SLEDAI. Results: We found that the A-cSLE patient was not Tregs deficient. The patient had increased frequency of Tregs and the Tregs/Teff ratio increased when the disease activity became less severe. CD4+ T-cells in the I-cSLE patient and in the A-cSLE patient with milder disease activity had heightened responsiveness to SEB, whereas T-cells were relatively hypo-responsive to SEB in the A-cSLE patient when disease activity was higher. The active patient exhibited higher frequencies of PD-1+ expressing Tregs, Teff and Tnaïve/mem cells under basal conditions compared to the HC and I-cSLE patient. Conclusions: In the A-cSLE patient, changes in Tregs/Teff ratio correlated better with clinical improvement compared to Tregs frequencies alone, and might reflect the restoration of immune homeostasis with therapy. SEB hypo-responsiveness in the A-cSLE patient when disease activity was higher paralleled with findings of greater frequencies of PD-1+ expressing Tregs, Teff and Tnaïve/mem cells, suggests a possible global exhaustion status of CD4+ T-cells in this patient.